Code-Switching and Code-Mixing in Everyday Interaction among Students of Daarul Rahman III Islamic Boarding School - Malewa, Asri Shafira (Litteratura: Jurnal Bahasa dan Sastra, 2025)
This study aims to identify the forms and types of code-switching and code-mixing used by ninth-grade female students at Darul Rahman 3 Islamic boarding school in Bojongsari. The research employs a qualitative descriptive method with three data collection techniques: observation, interviews, and documentation. The theoretical framework applied in this study is Dell Hymes’ theory of code-switching and Kridalaksana’s theory of code-mixing, which encompass external and internal code-switching, as well as code-mixing at the levels of words, phrases, and clauses. The findings indicate that there are six forms of code-switching and fifteen forms of code-mixing. Of the six identified instances of code-switching, five are external and one is internal. Meanwhile, of the fifteen instances of code-mixing, eleven occur at the word level, three at the phrase level, and one at the clause level. Code-switching in this study involves Indonesian, Arabic, and English, whereas code-mixing involves Indonesian and English.